The NUKDOS software for treatment planning in molecular radiotherapy = Die NUKDOS-Software für die Therapieplanung in der molekularen Radiotherapie - Kletting, Peter; Glatting, Gerhard (Zeitschrift für medizinische Physik, 2015)
The aim of this work was the development of a software tool for treatment planning prior to molecular radiotherapy, which comprises all functionality to objectively determine the activity to administer and the pertaining absorbed doses (including the corresponding error) based on a series of gamma camera images and one SPECT/CT or probe data. NUKDOS was developed in MATLAB. The workflow is based on the MIRD formalism. For determination of the tissue or organ pharmacokinetics, gamma camera images as well as probe, urine, serum and blood activity data can be processed. To estimate the time-integrated activity coefficients (TIAC), sums of exponentials are fitted to the time activity data and integrated analytically. To obtain the TIAC on the voxel level, the voxel activity distribution from the quantitative 3D SPECT/CT (or PET/CT) is used for scaling and weighting the TIAC derived from the 2D organ data. The voxel S-values are automatically calculated based on the voxel-size of the image and the therapeutic nuclide (90Y, 131I or 177Lu). The absorbed dose coefficients are computed by convolution of the voxel TIAC and the voxel S-values. The activity to administer and the pertaining absorbed doses are determined by entering the absorbed dose for the organ at risk. The overall error of the calculated absorbed doses is determined by Gaussian error propagation. NUKDOS was tested for the operation systems Windows® 7 (64 Bit) and 8 (64 Bit). The results of each working step were compared to commercially available (SAAMII, OLINDA/EXM) and in-house (UlmDOS) software. The application of the software is demonstrated using examples form peptide receptor radionuclide therapy (PRRT) and from radioiodine therapy of benign thyroid diseases. For the example from PRRT, the calculated activity to administer differed by 4% comparing NUKDOS and the final result using UlmDos, SAAMII and OLINDA/EXM sequentially. The absorbed dose for the spleen and tumour differed by 7% and 8%, respectively. The results from the example from radioiodine therapy of benign thyroid diseases and the example given in the latest corresponding SOP were identical. The implemented, objective methods facilitate accurate and reproducible results. The software is freely available.